An overview of the provision of Islam in children education - Adamu, Zakiyu Ubale; Abdul Hakim, Abdullah; Tahir, Abdurrahman (2015)
Background: Islamic education is clearly aimed at the total development of man physically, mentally, spiritually, intellectually and economically. Objectives: This study aimed to overview a provision of Islam in children education. It focused to identify how Islam cares about the children development as well as types of training responsibilities that Islam gave to parents to their children. Conversely, the study also aimed to highlight the measures that Islam took to prevent children‟s naughtiness. Methods: The study is descriptive in nature, employing Content analysis of the prime resources of Islamic jurisprudence: The Quran and Hadith (tradition of the Prophet Muhammad Pbh) were used as primary sources to carry out the study. Results: Research findings indicate that the provision of Islam in children education was aimed to develop them comprehensively involving all fundamental aspects of human being. This kind of training will ensure the success of the parents in developing their children with holistic and balanced manner. It also revealed that parents are the root element of their children‟s education. Conclusion: The research has an implication in the sense that it should be the parents‟ ladder in training their children base on the provision of Islam. In addition, the significant role that Islam played in educating the children should be the root of concern for all stakeholders in the community.